Agama, Kebudayaan, dan Kekuasaan: Catatan Teoritik dari Seorang Salafi - Muhammad Belanawane (Antropologi Indonesia, 2011)
Theoretical shifts in anthropological studies in recent decades has given way to renewed recognition of looking at issues of identity, namely that the sociall life, the arena in which the identity plays in, must be fundamentally understood as negotiating meanings. This is where Clifford Geertz’s interpretative approach becomes important yet problematic. Important because Geertz offers a humanistic approach which examines how meanings and symbols become important in the view of the community itself. Therefore, he argues, cultural interpretation requires a more in-depth analysis, also more intelligent and complex in which its purposes and those complexed cultural forms that can not simply be reduced to the effects on the social engines and organisms as claimed by structuralist and functionalist scholars before him. At the same time, it is also problematic because of Geertz’s position that searches for meaning makes him seem neglective or underestimative of the process of how interaction – the arena of where meanings work – is produced. In this case, Geertz’s critics have “helped” by reminding him of what is power relations and agency. Refering to the conception of Sherry Ortner, the author argues that through the agency there is a way to see this debate from the mid. The side which is not for eliminating the significant influence of Geertz is also not to ignore the significance of the critics’ arguments, but to bridge the two (meaning and power relations). Efforts in connecting this theory through the concept of agency consequently will include the significance of one party, at the same time improve its insignificance through the criticism of others and vice versa. Keyword: power relations, meanings, culture, religion, identity, agency